Neural imaginaries at work: Exploring Australian addiction treatment providers' selective representations of the brain in clinical practice. (June 2020) - Barnett, Anthony I.; Pickersgill, Martyn; Dilkes-Frayne, Ella; Carter, Adrian
Abstract: Although addiction neuroscience hopes to uncover the neural basis of addiction and deliver a wide range of novel neuro-interventions to improve the treatment of addiction, the translation of addiction neuroscience to practice has been widely viewed as a 'bench to bedside' failure. Importantly, though, this linear 'bench to bedside' conceptualisation of knowledge translation has not been attentive to the role addiction treatment providers play in reproducing, translating, or resisting neuroscientific knowledge. This study explores how, to what extent, and for what purpose addiction treatment providers deploy neuroscientific representations and discuss the brain in practice. It draws upon interviews with 20 Australian treatment providers, ranging from addiction psychiatrists in clinics to case-workers in therapeutic communities. Our findings elucidate how different treatment providers: (1) invoke the authority and make use of neuroscience in practice (2) make reference to neuroscientific concepts (e.g., neuroplasticity); and sometimes represent the brain using vivid neurobiological language, metaphors, and stories; and, (3) question the therapeutic benefits of discussing neuroscience and the use of neuroimages with clients. We argue that neurological ontologies of addiction, whilst shown to be selectively and strategically invoked in certain circumstances, may also at times be positioned as lacking centrality and salience within clinical work. In doing so, we render problematic any straightforward assumption about the universal import of neuroscience to practice that underpins narratives of 'bench to bedside' translation. Highlights: Interviews were conducted with 20 Australian addiction treatment providers. Addiction treatment providers selectively deploy neuroscience for therapeutic gain. The relevance of presenting neuroimages or neuroscience is at times questioned. Linear notions of 'bench to bedside' translation of neuroscience are oversimplified.